Innovation and the International Firm Structure: Theory and Evidence from German Firm-Level Data - Thorsten Hansen (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
This paper studies the impact of innovation on the organizational structure. The theoretical framework predicts that a larger parental pool of knowledge raises the probability of oshoring. This holds in a national as well as an international context. However, when the producer loses territorial protection, the changeover from non-integration to integration is delayed. Employing data on German rms investing in Eastern Europe nds empirical evidence for the theoretical predictions. The results are robust to dierent measurements and an instrumental variable regression.
urn:nbn:de:bvb:19-epub-11464-6
Keywords: D23; D51; F23; L14; L21; L22; L23; 330; offshoring; innovation; firm structure; Innovation; Multinationales Unternehmen; Organisationsstruktur; Auslandsverlagerung; Patentrecht; Unternehmenszentrale; Ausländische Tochtergesellschaft; Theorie; Schätzung; Deutschland; Osteuropa